2013
DOI: 10.1002/2013jb010532
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of the Izu collision zone in central Japan from seismic refraction data

Abstract: [1] The Izu-Bonin arc (IBA) has been colliding with the more northerly Honshu arc since the middle Miocene, forming a globally unique active Izu arc-arc collision zone (ICZ) in central Japan. To determine crustal structure of the ICZ, we constrain P and S wave velocities from active source refraction data. The velocity structures reveal that the style of collisions of the Misaka, Tanzawa, and Izu blocks, which were derived from the IBA, has been controlled by subduction of the IBA. High-velocity rocks (Vp > 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…The cluster activity of 2012 seems to have occurred on a plane dipping to the SE with a NE-SW strike (Fig. 5), and the source area was located in the deeper extension of the SE-dipping Sone Hills faults (Arai et al 2013). This is also consistent with the tectonic characteristics of this region.…”
Section: Temporal Change In the Rigidity And Attenuationsupporting
confidence: 71%
“…The cluster activity of 2012 seems to have occurred on a plane dipping to the SE with a NE-SW strike (Fig. 5), and the source area was located in the deeper extension of the SE-dipping Sone Hills faults (Arai et al 2013). This is also consistent with the tectonic characteristics of this region.…”
Section: Temporal Change In the Rigidity And Attenuationsupporting
confidence: 71%
“…Numerical values in the plot are P wave velocities estimated from first arrival times. For deeper parts (in parentheses), we assumed velocities using the surrounding experiments (Arai et al 2009(Arai et al , 2013. Note that this reflective zone is located at the down-dip end of the strongly coupled plate boundary (see also Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used active-source data whose shot points are shown by red stars. Previous studies in the collision zone include seismic profiles whose shot points are indicated by yellow stars Arai et al 2009), green stars (Arai et al 2013), and blue stars . Record sections of SP-W1, SP-W5, and SP-E4 are shown in Figs.…”
Section: Introductionmentioning
confidence: 99%
“…From reflection analysis of the western profile, Sato et al (2006) found an aseismic slab beneath the Misaka and Tanzawa blocks at a depth of 30 to 35 km, along which the IBA middle/lower crust subducts (Arai et al 2009). Refraction analysis using the same data set (Arai et al 2013) revealed that the overall geometry of the collisional boundaries is that of a doubly vergent system (e.g., Willett et al 1993), which is characterized by inward-dipping reverse faults on both sides. Arai et al (2013) also showed that Miocene granitic plutons with high seismic velocities that intrude into the Honshu arc crust and accreted crustal blocks of the IBA (Tanzawa block) form the Kofu granitic complex (KGC) and the Tanzawa plutonic complex (TPC), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Refraction analysis using the same data set (Arai et al 2013) revealed that the overall geometry of the collisional boundaries is that of a doubly vergent system (e.g., Willett et al 1993), which is characterized by inward-dipping reverse faults on both sides. Arai et al (2013) also showed that Miocene granitic plutons with high seismic velocities that intrude into the Honshu arc crust and accreted crustal blocks of the IBA (Tanzawa block) form the Kofu granitic complex (KGC) and the Tanzawa plutonic complex (TPC), respectively. Petrological investigations have suggested that these intrusive rocks formed by syncollisional magmatism of the IBA crust that subducted beneath the Honshu arc (Saito et al 2007;Tamura et al 2010;Tani et al 2010).…”
Section: Introductionmentioning
confidence: 99%